Diet of terrestrial anurans in an ephemeral and simplified habitat during the dry season in the Brazilian Cerrado. Issue 6 (1st November 2020) - Brandão, Reuber A.; Fenker, Jéssica; Lopes, Bruno E. Pires de Carmago; de Sena, Vitor M. de Alcantara; Vasconcelos, Beatriz D.
Abstract : Amphibians often use ephemeral and simplified habitats during dry seasons in tropical biomes. These simplified habitats can have less prey available, but only a few studies focus on how their use affects frogs' diet. Here we studied the diet of three terrestrial frogs ( Adenomera sp., Ameerega berohoka, and Rhinella ocellata ) at a riverbank exposed only during the dry season in the Brazilian Cerrado biome. Diets overlapped more than expected by chance and were composed mainly of social insects (ants and termites). Prey volumes were not related to the size of frogs or their head measurements. Frogs at the riverbank ingested less prey categories and fewer prey items in comparison to studies conducted in more stable and complex environments. We suggest that frogs were attracted to riverbanks by the humidity and availability of reproductive sites, opportunistically ingesting prey available in the habitat. The abundance of social insects allowed the presence of frogs specialized in ants, such as the bufonid Rhinella ocellata and the dendrobatid Ameerega berohoka .